The dean's December - Bellow, Saul. (London : Penguin Books, 2008)
Albert Corde, newspaperman turned academic, accompanies his wife to visit her dying mother in Bucharest. At home in Chicago, his magazine articles and involvement in a student murder scandal have him in the middle of a raging controversy.
Young Adult.
Young Adult
Keywords: College teachers -- Illinois -- Chicago -- Fiction; Mothers and sons -- Romania -- Fiction; College stories